2011
DOI: 10.1007/s13224-011-0042-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality in an urban tertiary care hospital of north India

Abstract: Objectives: The aims of the study were to help generate information and knowledge regarding the causes and complications leading to maternal deaths (MDs) in an urban tertiary care hospital, to find if any of them are potentially preventable, and to use information thus generated to save lives. Methods: The medical records of all MDs occurring over a period of 4 years between January 2003 and December 2006 were reviewed and correlated with maternal age, antenatal registration, mode of delivery, parity, admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
40
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 2 publications
5
40
3
Order By: Relevance
“…Similar results with hypertensive disorders complicating pregnancies as the leading cause of maternal death have been found with Mukherjee et al - 22.97% of deaths due to toxaemia, Puri et al -18%, Prashantha R -50.56%, Ritalal et al -20%, Sulthan S et al also had increased maternal deaths due to gestational hypertension -39.64%, Bhaskar et al had an equal incidence of hypertension and haemorrhage as the cause of maternal death -26.66%. 13,15,16,[21][22][23] As per WHO 2010, 25%of all maternal deaths are due to haemorrhage while in our study 31% of the maternal deaths were due to haemorrhage.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Similar results with hypertensive disorders complicating pregnancies as the leading cause of maternal death have been found with Mukherjee et al - 22.97% of deaths due to toxaemia, Puri et al -18%, Prashantha R -50.56%, Ritalal et al -20%, Sulthan S et al also had increased maternal deaths due to gestational hypertension -39.64%, Bhaskar et al had an equal incidence of hypertension and haemorrhage as the cause of maternal death -26.66%. 13,15,16,[21][22][23] As per WHO 2010, 25%of all maternal deaths are due to haemorrhage while in our study 31% of the maternal deaths were due to haemorrhage.…”
supporting
confidence: 88%
“…13,15,16,[21][22][23] As per WHO 2010, 25%of all maternal deaths are due to haemorrhage while in our study 31% of the maternal deaths were due to haemorrhage. 3 Similar results had been found in various studies such as Arpita N et al has a 31.9% of deaths due to haemorrhage, Vidyadhar et al has a 21.05% of deaths due to haemorrhage, Verma A et al has a 21.8% of maternal death due to haemorrhage, Boro et al has 25% of maternal death due to haemorrhage.…”
mentioning
confidence: 71%
“…Our finding is in line with several other studies that suggest pre-existing anemia is a major contributory factor of direct obstetrical deaths due to PPH and sepsis and early detection of anemia and its treatment along with institutional delivery can prevent and ensure timely management of PPH thus saving lives. 22,23 Age at time of index pregnancy, at time of marriage, age at first conception and gravida were not found to be significant risk factors due to maternal death. This can be partly explained as these factors could probably be present in both the mothers who survived as well as those who died due to post-partum haemorrhage and acted as risk factors for the development of PPH.…”
Section: Discussionmentioning
confidence: 81%
“…In the study, we found most common cause of maternal deaths in TMCH is due to Anaemia (28.85%) which is multifactorial in origin. Mukherjee 9,12 This is mainly due to irregular ANCs and lack of compliance to treatment in the patient's study group. Obstructed labour (9.61%), Sepsis (9.61%), Unsafe Abortion (3.84%) and others (3.84%) comes in magnitude as causes leading to maternal deaths in TMCH, Tezpur.…”
Section: Resultsmentioning
confidence: 99%